Development of strategic decision in business expansion: Utilizing SWOT, VRIO, and PESTEL in GNS Strategy Formulation - Simamora, Raynhard Takkas Manahan; Siallagan, Manahan Parlindungan Saragih (JURNAL MANAJEMEN MOTIVASI, 2025)
After the COVID-19 pandemic, Indonesia's telecommunications industry faces significant growth challenges due to declining demand for home internet services as people's activity patterns evolve. This shift has directly impacted the business performance of Global Network Service (GNS), a unit of X Corporation highly dependent on telecommunications operators as the primary customer segment. The company's reliance on a stagnating market threatens its long-term sustainability and growth. This study aims to develop a business diversification strategy for GNS targeting Indonesia’s enterprise market to achieve sustainable growth, improve competitiveness, and reduce dependency on the shrinking telecommunications sector. Using a qualitative case study approach, the research utilizes primary data from semi-structured interviews with GNS stakeholders, alongside secondary data from industry reports, company documents, and national policy publications. The analysis utilizes VRIO, SWOT, PESTEL, and Porter’s Five Forces frameworks to assess internal competencies and external market dynamics. The results show that GNS has some competitive advantages, such as a strong global reputation and technical skills in networking and cybersecurity. However, challenges include low brand awareness in the enterprise sector and slow decision-making processes. The recommended strategy involves four pillars: transforming service models, restructuring the organization, leveraging global reputation for premium solutions, and establishing a Security Operations Center (SOC) ecosystem as a competitive edge.